2004
DOI: 10.1007/s10067-004-0919-2
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the renal outcome of pediatric lupus nephritis

Abstract: The aim of this study was to analyze the renal outcome of pediatric lupus nephritis in the past two decades. We retrospectively reviewed the medical records of patients who fulfilled the 1987 American Rheumatism Association revised criteria for systemic lupus erythematosus who were followed up at the National Taiwan University Hospital between 1980 and 2001. All new patients who were under 18 years of age at the time of diagnosis were enrolled and were followed up until death, loss to follow-up, or till the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 10 publications
5
30
1
5
Order By: Relevance
“…This suggests that the higher incidence of hypertension among our patients might be due to a difference in our patient selection criteria. Otherwise, the incidence of proteinuria, macroscopic hematuria and the distributions of the WHO classes in our patients were very similar to those of most other studies [14,17,18].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that the higher incidence of hypertension among our patients might be due to a difference in our patient selection criteria. Otherwise, the incidence of proteinuria, macroscopic hematuria and the distributions of the WHO classes in our patients were very similar to those of most other studies [14,17,18].…”
Section: Discussionsupporting
confidence: 91%
“…Although the data suggested that we had a higher percentage of hypertensive patients than in most other pediatric studies [13,14,17], these studies included patients with class II lupus nephritis, which made comparison with our study very difficult. However, another recent study from Taiwan that included only patients with severe lupus nephritis reported an incidence of 54% hypertensive patients before treatment [18]. This suggests that the higher incidence of hypertension among our patients might be due to a difference in our patient selection criteria.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Among the additional 26 patients without renal biopsies, four died within the same observation period. Both the patient and renal survival rates among our study cohort were similar to or better than those reported in several other pediatric series during the past decade [5,22,23,26,28,29,33]. Contrary to expectation, neither renal histology, including the WHO classification and the activity and chronicity indices, nor any other sign or symptom was independently correlated with the outcome.…”
Section: Discussionsupporting
confidence: 84%
“…Based on the results of this retrospective study, patient and renal survival rates among Iranian children with biopsyproven LN are high at the mid-term follow-up compared to those reported for other countries [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%